In Silico Modeling of Novel Drug Ligands for Treatment of Concussion Associated Tauopathy. Issue 10 (12th July 2016) - Zhao, Wei; Ho, Lap; Wang, Jun; Bi, Weina; Yemul, Shrishailam; Ward, Libby; Freire, Daniel; Mazzola, Paolo; Brathwaite, Justin; Mezei, Mihaly; Sanchez, Roberto; Elder, Gregory A.; et al.
ABSTRACT: The objective of this study was to develop an in silico screening model for characterization of potential novel ligands from commercial drug libraries able to functionally activate certain olfactory receptors (ORs), which are members of the class A rhodopsin‐like family of G protein couple receptors (GPCRs), in the brain of murine models of concussion. We previously found that concussions may significantly influence expression of certain ORs, for example, OR4M1 in subjects with a history of concussion/traumatic brain injury (TBI). In this study, we built a 3‐D OR4M1 model and used it in in silico screening of potential novel ligands from commercial drug libraries. We report that in vitro activation of OR4M1 with the commercially available ZINC library compound 10915775 led to a significant attenuation of abnormal tau phosphorylation in embryonic cortico‐hippocampal neuronal cultures derived from NSE‐OR4M1 transgenic mice, possibly through modulation of the JNK signaling pathway. The attenuation of abnormal tau phosphorylation was rather selective since ZINC10915775 significantly decreased tau phosphorylation on tau Ser202/T205 (AT8 epitope) and tau Thr212/Ser214 (AT100 epitope), but not on tau Ser396/404 (PHF‐1 epitope). Moreover, no response of ZINC10915775 was found in control hippocampal neuronal cultures derived from wild type littermates. Our in silico model provides novel means to pharmacologically modulate select ubiquitously expressed ORs in the brain through high affinity ligand activation to prevent and eventually to treat concussion induced down regulation of ORs and subsequent cascade of tau pathology. J. Cell. Biochem. 117: 2241–2248, 2016. © 2016 Wiley Periodicals, Inc.